Effect of Cocoa Bean Fermentation Using Lactic Acid Bacteria and Yeast Starters on Flavonoid Formation and Antioxidant Activity - Anja Meryandini; Irvan Anwar; Titi Candra Sunarti (Microbiology Indonesia, 2023)
This study investigates the effect of fermentation using lactic acid bacteria and yeast as starters on the formation of flavonoid compounds and the antioxidant activity of cacao beans. The fermentation process were divided into 4 groups: F1: spontaneous fermentation, F2: fermentation using Lactic Acid Bacteria (LAB), F3: fermentation using yeast and F4: fermentation using LAB and yeast. The extraction process was done using ethanol. Flavonoid content was analysis using spectrophotometer assay. The antioxidant activity was analyzed by 1,1-difenil-2-pikrilhidrazil (DPPH) method. All ethanol extract samples of fermented cacao beans contained alkaloids, polyphenols, flavonoids, and tannins. The flavonoid compounds from ethanol extract of cacao beans in F1 is 4.35 ± 0.20 mg/L, F2 (5.64 ± 0.05), F3 (5.37 ± 0.17), and F4 (5.99 ± 0.23 mg/L). The antioxidant activity of cacao bean fermentation extracts using starter were increase compared to the spontaneous fermentation extract (F1). The antioxidant activity in F2 increased to 46.45 ± 2.00%, F3 (49.05 ± 0.58%), and F4 (50.33 ± 0.43%), while the antioxidant activity of F1 was 42.31 ± 0.66%. IC50 value as the ability of the extract to reduce 50% DPPH radical on the ethanol extract of cacao beans from spontaneous fermentation (F1) was 141.67 mg/L. The IC50 value of the fermented cacao bean extract with the addition of starter was obtained at F2 at 109.30 mg/L, F3 (97.51), and F4 is 88.15 mg/L.